Aceh Exhibition Center with an Iconic Concept Approach Cultural Symbol theme - cut nora ernanda (Universitas Syiah Kuala, 2019)
AbstractProgress in the field of business and tourism is very important in an area and is supported by activities to promote the existing potential through meetings, incentives, conventions, exhibitions (MICE). Aceh is one of the many provinces in Indonesia that plays a role in realizing MICE and is trying to present exhibition activities to promote Aceh overseas. The thing to be shown in realizing the iconic design of the theme taken is the cultural symbol, which in this design can show cultural symbols or identities as well as the characteristics of the Aceh region. The choice of location is located on Jl. Taman Sri Ratu Syafiatuddin, Kuta Alam District, Banda Aceh supports the achievement of the iconic approach by taking on the characteristics of the surrounding buildings. This design provides many facilities for activities according to the exhibition function by displaying sequences in the building circulation so that it can give a certain impression to visitors of the building.